1996
DOI: 10.1021/ic951270z
|View full text |Cite
|
Sign up to set email alerts
|

Factors Affecting Solution Properties of Vanadium(V) Compounds:  X-ray Structure of β-cis-NH4[VO2(EDDA)]1

Abstract: The solution properties of two isomeric forms of the V−EDDA complex (the symmetric α-cis and asymmetric β-cis) have been studied using multinuclear NMR spectroscopy. The isomerization constant of the aqueous equilibrium mixture expressed as [α-cis]/[β-cis] increased on the addition of organic solvents (methanol, formamide, and DMSO) and decreased on the addition of salts (NaCl, NaClO4, and NH4Cl). The isomerization constant and corresponding thermodynamic parameters were determined under a variety of condition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
33
0

Year Published

2001
2001
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(37 citation statements)
references
References 44 publications
4
33
0
Order By: Relevance
“…The O-V-O angle in the VO 2 moiety is similar to those previously reported for related complexes with nitrogen trans to the oxo groups, for example, the a-cis isomer of the EDTA complex [24] and b-cis isomer of the EDDA complex. [18] Other authors [25] also found a rather similar type of isomerism and used the notation cis-and trans-phenolates. Hereafter we will use the a-cis and b-cis notation; however, as will be clear below, in solution the V V ±Rpyr 2 en system is much more complex, because several a-cis and b-cis complexes form.…”
Section: Introductionmentioning
confidence: 84%
See 2 more Smart Citations
“…The O-V-O angle in the VO 2 moiety is similar to those previously reported for related complexes with nitrogen trans to the oxo groups, for example, the a-cis isomer of the EDTA complex [24] and b-cis isomer of the EDDA complex. [18] Other authors [25] also found a rather similar type of isomerism and used the notation cis-and trans-phenolates. Hereafter we will use the a-cis and b-cis notation; however, as will be clear below, in solution the V V ±Rpyr 2 en system is much more complex, because several a-cis and b-cis complexes form.…”
Section: Introductionmentioning
confidence: 84%
“…The white precipitate was filtered, washed with water, ethanol, and diethyl ether, and dried under vacuum. Yield: 60 %; elemental analysis calcd (%) for C 18 ). From the solution of the filtrate, kept at room temperature for two weeks, colorless crystals were collected and characterized by Xray diffraction.…”
Section: Synthesis Of the Ligandsmentioning
confidence: 99%
See 1 more Smart Citation
“…10 In solution ethylenediaminediacetate (EDDA) ligand forms two isomers of similar stability with vanadium(V), a symmetric α-cis complex and an asymmetric β-cis complex. 10,14 In a previous paper, 15 we reported that the vanadium complex of propylenediaminetetraacetate (PDTA) ligand was determined to have α-cis structure in solid. The anion [VO 2 PDTA] 3− has a slightly irregular octahedral geometry in which two oxo ligands are cis to each other as shown in EDTA, 7,8 and EDDA complexes.…”
Section: Introductionmentioning
confidence: 99%
“…But ethylenediaminediacetate (EDDA) is known to form a β-cis structure (2) with vanadium(V). 11 According to the solution studies, 11,12 EDDA forms α-cis and β-cis isomers with vanadium(V) while EDTA forms only the α-cis isomer with vanadium(V). The steric hindrance makes stable the α-cis form of the isomers because the substitution of an acetate group on nitrogen increases steric bulk.…”
mentioning
confidence: 99%